Conformal transformation for prescribing scalar curvature on sphere (2010)
Granados, in [1], has demonstrated the existence of a family of metrics conforming to the usual one of the unitary sphere with scalar curvature n (n − 1). In the present article another solution is found to the problem of prescribing the scalar curvature of Sn by means of a suitable conformal transformation. Moreover, if a family of solutions to the general problem were known, another family of solutions would be obtained.